Knowledge Control Model of Distance Learning System “Kherson Virtual University” - Kravtsov, Г.М.; Kravtsov, Д.Г. (Journal of Information Technologies in Education (ITE), 2007)
The results of designing and modeling of distance testing system on the base of international standards IMS, SCORM are represented. Distance testing system “Web-Examiner” is used for the illustration.